The effect of performance based grant on research and development at Pakistani Public Universities - Abbas, Zaheer (2019)
Higher education sector of every country has a significant contribution in the development of the society. Similarly, it plays a vital role in the research and development for the prosperity and improvement in social and educational settings. Furthermore, R&D lies under the higher education sector of education system. Government and universities are usually responsible to provide funds and opportunities to facilitate the research progress. But, the education system cannot run if the aforementioned authorities fail to provide sufficient funding. However, since the last few years government of Pakistan has deducted and reduced the performance grant and development budget, which were allocated for higher education institutions. Therefore, this study focused on the performance based grant which is allocated on the base of research outcome of the universities. This research has been conducted to analyze the effect of performance based grant in Pakistani public universities and its impact on research and development performance. Meanwhile, it’s also determined the relationships between performance based grant and R&D performance through the mediating role of goal conflict and information asymmetry. Agency theory is used to support this research as a theoretical framework which aids to analyze the relationship between government (Principal) and the universities (agents) in the context of higher education. In this study both qualitative and quantitative research approaches have been adopted, by implying an exploratory sequential design. Firstly, the qualitative data have been collected through semi-structured interviews from head of departments and treasury officers of Pakistani public universities. On the other hand, the survey questionnaire for quantitative data collection was designed based on the results which acquired through the qualitative approach and from the previous research. The quantitative data was analyzed by using statistical Package for social science (SPSS) version 23 and Smart PLS 3.2.7, Partial Least Square Structural Equation Modeling software. This research study facilitates the HEC office (policy makers, finance officers etc.) regarding the validity, effectiveness and utilization of performance based grant to examine the effects on R&D performance in higher education sectors. Similarly, the findings of this research indicated that by decreasing the conflicts and uncertainties between the institutions under higher education commission of Pakistan for improving the quality of teaching and outcome based research.